Texture‐modified foods and thickened fluids used in dysphagia: Israeli standardised terminology and definitions. Issue 6 (10th July 2018) - Icht, M.; Bergerzon‐Bitton, O.; Kachal, J.; Goldsmith, R.; Herzberg, O.; Endevelt, R.
Abstract: Background: Texture‐modified foods and thickened fluids are used as a strategy that aims to compensate for dysphagia and improve the safety and efficiency of swallowing. Currently, in Israel, there are no standardised terminologies and definitions for texture‐modified diets. The inconsistent terminology adversely affects patient safety and the efficiency of communication between staff members both within and between health institutions. This present study describes a project of the Israeli Ministry of Health in which the labels and definitions of prevalent foods and fluids used in health institutions are mapped to develop a consensus on national standards. Methods: A multidisciplinary committee of speech‐language pathologists (SLPs) and registered dietitians (RDs) was appointed. A questionnaire was developed to identify the labels of texture‐modified foods and fluids used in the Israeli healthcare system. The questionnaire included questions on knowledge, attitudes and barriers related to the need for a consistent national terminology for texture‐modified diets. Questionnaires were sent to 120 institutions. The project was conducted between September 2016 and December 2017. Results: Twenty‐six SLPs and 42 RDs responded. The answers revealed that there were 50 labels in use for texture‐modified foods. When asked to describe the texture of a particular food item, up to 17 different labels were used. There was broad support for a standardised terminology. Conclusions: The results of the present study confirm the lack of national standards in clinical practice and the need for a consistent terminology. A consensus was achieved between the committee members and the committee adopted the International Dysphagia Diet Standardization Initiative (IDDSI) recommendations and adapted the terminology to Hebrew.